Car Free Day sebagai Ajang Pemberdayaan UMKM dalam Mendukung Agenda Pembangunan Berkelanjutan - Muhammad Reza Pahlawan; Juwita Sari; Titik Mildawati; Wimba Respatia (Universitas Nurul Jadid, 2024)
Village’s Sustainable Development Goals (SDGs) is an indicator used to retrieve the village's development performance. This indicator was applied to all villages in Indonesia, including Yosowilangun in Gresik Regency. This village has low scores on indicators related to economics. This needs to be a concern because the village's potential to become an economically independent village is quite high. This potential is reflected in the number of registered Micro, Small, and Medium Enterprises (MSMEs). The village officials are also active in helping to empower them in terms of capital. However, this is still not effective because the indicator value for Equitable Village Economic Growth is only 34.96. Apart from that, the participation rate is also still low, with only around 10%. This is caused by the difficulty of finding the markets. Car Free Day is considered capable of solving this problem. Therefore, this service activity is carried out by providing assistance to related parties to analyze the CFD urgencies. The main focus is an analysis document that can be used to simplify the implementation process. The results of the study indicate that Yosowilangun Village is capable of holding a CFD if seen from the prospective location, potential visitors, and potential demand.